2004
DOI: 10.1149/1.1635388
|View full text |Cite
|
Sign up to set email alerts
|

Arrhenius Characterization of ILD and Copper CMP Processes

Abstract: To date, chemical mechanical planarization ͑CMP͒ models have relied heavily on parameters such as pressure, velocity, slurry, and pad properties to describe material removal rates. One key parameter, temperature, which can impact both the mechanical and chemical facets of the CMP process, is often neglected. Using a modified definition of the generalized Preston's equation with the inclusion of an Arrhenius relationship, thermally controlled polishing experiments are shown to quantify the contribution of tempe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(55 citation statements)
references
References 11 publications
2
53
0
Order By: Relevance
“…According to the Arrhenius equation and Sorooshian's study [10], the process temperature in the copper CMP process affects the chemical reaction rate. To study the relation between polishing temperature and chemical reaction rate, we measured the static etch rates at various slurry temperatures, and the results are shown in Fig.…”
Section: Thermal Effect On Chemical Reactionmentioning
confidence: 99%
See 2 more Smart Citations
“…According to the Arrhenius equation and Sorooshian's study [10], the process temperature in the copper CMP process affects the chemical reaction rate. To study the relation between polishing temperature and chemical reaction rate, we measured the static etch rates at various slurry temperatures, and the results are shown in Fig.…”
Section: Thermal Effect On Chemical Reactionmentioning
confidence: 99%
“…The static etch rates were measured at five points in each sample, and it was found that the rate increased with the slurry temperature. The Arrhenius equation for the static etch rate can be rewritten for the CMP process as follows [10]:…”
Section: Thermal Effect On Chemical Reactionmentioning
confidence: 99%
See 1 more Smart Citation
“…The focused thermal zone was selected on the polishing pad adjacent to the wafer-pad interface to record the average temperature. Since the temperature in this interface between wafer and polishing pad cannot be obtained directly, the selected zone is the best approximation of the average process temperature [20]. These three process variables are good indicators of chemical-mechanical polishing conditions [21], [22].…”
Section: Application To Identification Of Interaction Structure mentioning
confidence: 99%
“…The slurry acts as a coolant material at the interface of the pad and wafer contact and takes away a significant part of the heat through convective heat transfer [42], [55], [56], [66]. The dissipated heat changes the chemical kinetics and the physical properties of the polishing pad [42], [55], [66].…”
Section: Introductionmentioning
confidence: 99%